Proceedings of the First European Symposium on Mathematics in Industry - European Symposium on Mathematics in Industry (1st : 1985 : Amsterdam); Hazewinkel, Michiel; Mattheij, Robert M. M.; Groesen, Embrecht W. C. van (Dordrecht : Kluwer, 1988)
05